Negation in Berber: variation, evolution, and typology - (:unkn) unknown (My University, 2020)
Double and triple negation marking is an ancient and deep-rooted feature that is attested in almost the entire Berber-speaking area (North Africa and diaspora), regardless of the type of negators in use; i.e. discontinuous markers (preverbal and postverbal negators) and dedicated negative verb stem alternations. In this article, we deal with the main stages that have led to the present Berber negation patterns and we argue, from a typological viewpoint, that certain morphophonetic mechanisms are to be regarded as a hitherto overlooked source for new negators. Moreover, we present a number of motivations that account for the hypothesis that, in Berber, those languages with both a preverbal and a postverbal negator belong to a diachronic stage prior to the attested languages with a preverbal negator only. Consequently, the study demonstrates that the Jespersen Cycle is back to the beginning in certain Berber languages. In doing so, we also show that Berber is to be regarded as a substrate in the development of double negation in North African Arabic. In addition, the study accounts for the asymmetric nature of Berber negation, although some new developments towards more symmetrical negation configurations are also attested.
Keywords: African Research